The Role of The Holy Spirit in Discipleship - James Kwang Jin Kim (STT Saint Paul Bandung, 2023)
A new believer in Jesus can't grow in faith without going through a discipleship process that relies on the power of the Holy Spirit. A disciple of Christ can only grow in the truth of the Word when guided by relying on the guidance of the Holy Spirit. After conducting a descriptive method study in this research by observing Acts 1:8 and Matthew 28:19-20, it shows that people who are discipled under the leadership of the Holy Spirit can grow, walk in the truth of God's word, be obedient and faithful in their faith in Jesus Christ.